PENGEMBANGAN LKPD BERBASIS KONTEKS PRIBADI PADA MATERI PELUANG KELAS VIII - Wisnu Siwi Satiti; Siti Nur Lailiyah (EDUSCOPE: Jurnal Pendidikan, Pembelajaran, dan Teknologi, 2022)
There are many students that have difficulties in learning mathematics. One of them is dueto lack of meaningful learning in mathematics-classroom, so that students' learning motivation is low. Learning becomes meaningful if the concepts are presented as contexts or situations in which students "experience" themselves. The use of mathematics in everyday life is the main idea of ​​mathematical literacy. Context of daily life that is closest to students is personal context. One of the mathematical materials that is widely applied to solve problems in everyday life is the concept of probability. Therefore, it is necessary to increase the use of personal context as a mathematical activity in learning probability. Mathematics activities can be presented with the use of teaching materials, one of which is Student-Worksheet. Thus, in this study, Student-Worksheet on the concept probability is developed by employing personal context. This study is a research-design within ADDIE model (analysis, design, development, implementation, evaluation). This study produces a product in the form of Student-Worksheet based on personal context for Probability for 8th graders. The results of this study shows that the Student-Worksheet developed is valid and practical. In addition, based on the results of the implementation phase, it shows that the Student-Worksheet is effective in facilitating students’understanding on the concept of probability.